(untitled) (Research, Society and Development, 2021)
This paper aimed to evaluate the impact of intercropping between oats and triticale species, over three defoliation cycles. The experiment occurred in two winters in a row, and was in split-plot randomized complete blocks design (20 plots) with five species combination, four blocks and three defoliations. The main plots were the species combination: black oat (Avena strigosa cv. IAPAR 61) – BO, white oat (Avena sativa cv. IPR Emerald) – WO, triticale (X Triticosecale Wittmack cv. Tpolo 981) – T; and the intercropping: black oat + triticale – BOT, and white oat + triticale - WOT. The sub-plots were the three defoliations cycles initially scheduled to be every 28 days. The intercropping between oats and triticale did not affect the accumulated dry matter yield (DM), but it also improved the pastures, as an increase on crude protein content (CP) (about 1.85% greater in WOT than WO; and 2.7% greater in BOT than BO). The number of leaves was also increased by the intercropping, from 4.2 (WO) and 3.7 (BO) to 7.6 (WOT) and 7.2 (BOT) leaves per main stem. Over the defoliation cycles, the maximum average of growth rate (2.72 t DM ha-1 ºCd-1), tiller per plant (10 tillers plant-1) and main tiller height (53.2 cm) were unanimously observed at third defoliation. The changes observed did not reduced the nutritional quality of the pastures, therefore both are highly indicated to these conditions.